General morbidity prevalence in the Delhi slums - Marimuthu P; Meitei M; Sharma BBL (Wolters Kluwer Medknow Publications, 2009)
Research Question: What is the sickness prevalence in the slums of a metropolitan city? Objectives: To estimate the morbidity prevalence with reference to a socio-economic and demographic perspective of the slum population of Delhi. Study Design: A cross-sectional study was conducted and data were collected by a two-stage random sampling method. In the first stage, slum locations were selected and in the second stage households were selected. Participants: Data were collected from 1049 households consisting of 5358 individuals′ information. Results: The overall morbidity prevalence is 15.4%. It is 14.7 and 16.3% for males and females, respectively but the differences are not statistically significant. The reported higher morbidity prevalence and the illiteracy status are significantly associated. Diseases of the respiratory system appear to be very high among slum dwellers. Conclusion: From this study, it can be concluded that the number of years of staying in the slum area, presence of a separate kitchen, type of house, it being Pucca or Kuccha, types of toilet pits or open defecation are the important environmental factors for the reports of higher morbidity patterns from the slum area.